Diseño de un sistema de producción sostenible para la elaboración de abono orgánico a partir de cáscaras de cacao y pseudotallos de plátano - Muñoz Pincay , Bryan Gabriel (2024)
The present research work proposes the design of a sustainable production system for the elaboration of organic compost, using cocoa husks and banana pseudostems as raw materials. This innovative approach aims to mitigate the environmental impact of organic waste, promote a circular economy model, and encourage more environmentally friendly agricultural practices. Through a comprehensive market study, existing opportunities and challenges in the organic fertilizer sector were identified. Subsequently, an efficient operations system was designed, detailing the production processes, necessary machinery and equipment, as well as the optimal plant distribution. The financial evaluation, including indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C), and Incremental Profitability Index (IPI), supports the economic viability of the project, demonstrating that it is possible to obtain economic benefits while adopting sustainable practices.